The Influence of Entrepreneurial Orientation on Business Continuity Performance with Resourcefulness as a Mediator and Technology Orientation as a Moderator\: A Study on Micro-Scale Coffee Shops in Central Java Province - Muhammad Arif Surana (International Forum of Researchers and Lecturers, 2026)
Micro, Small, and Medium Enterprises (MSMEs), especially micro-scale coffee shops, face various challenges in maintaining business continuity amidst increasingly fierce competition and dynamic business environments. This study aims to analyze the effect of Entrepreneurial Orientation on Business Continuity Performance with Resourcefulness Architect as a mediating variable in micro-scale coffee shops in Central Java Province. The study uses a quantitative explanatory approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through distributing questionnaires to 184 micro-scale coffee shop owners selected using a purposive sampling technique. The results show that Entrepreneurial Orientation has a positive and significant effect on Resourcefulness Architect and Business Continuity Performance. In addition, Resourcefulness Architect also has a positive and significant effect on Business Continuity Performance and is proven to partially mediate the relationship between Entrepreneurial Orientation and Business Continuity Performance. These findings indicate that the ability of entrepreneurs to creatively manage, combine, and utilize resources is an important mechanism that strengthens the influence of entrepreneurial orientation on business sustainability. This research contributes to the development of the literature on Business Continuity Performance through the integration of the Resource-Based View, Resource Orchestration Theory, and Dynamic Capabilities Theory perspectives, and provides practical implications for MSMEs in strengthening their entrepreneurial orientation and resource management capabilities to increase business resilience.